The Flavonoids Casticin and Artemetin Are Poorly Extracted and Are Unstable in an Artemisia annua Tea Infusion - Weathers, Pamela J.; Towler, Melissa J. (Planta Medica, 2012)
A number of flavonoids including casticin and artemetin from Artemisia annua have shown synergism with artemisinin against Plasmodium falciparum, but it is unclear if the flavonoids are also extracted into a tea infusion of the plant. Using a tea infusion preparation protocol that was reported to be highly effective for artemisinin extraction, we measured casticin and artemetin extraction. There was only a 1.8 % recovery of casticin in the infusion while artemetin was undetectable. After 24 hr storage at room temperature, casticin yield declined by 40 %. These results show that although a tea infusion of the plant may extract artemisinin, the polymethoxylated flavonoids casticin and artemetin are poorly extracted and lost with storage at room temperature and thus, the tea infusion appears to lose synergistic value.
Keywords: casticin; artemisinin; malaria; stability; tea infusion; Artemisia annua; Asteraceae; Compositae